The Foreign Investor Bias and Its Linguistic Origins - Lundholm, Russell; Rahman, Nafis; Rogo, Rafael (Management Science, 2018)
We study how misaligned language between the investor and the firm contributes to the underweighting of foreign securities in an international portfolio. In particular, we document a significant U.S. institutional investor bias against firms located in Quebec relative to firms located in the rest of Canada (ROC). The differential bias is surprising given that (i) Quebec and the other Canadian provinces share the same nationality, federal law, stock exchange, and accounting standards; (ii) their regulatory filings are prepared in English and French; and (iii) U.S. institutional investors are sophisticated and located close to Quebec and the ROC. We also examine Quebec firms with different levels of French versus English online presences as well as those with CEOs who have U.S. work experience or board members or financial analysts who reside in the United States. We find that each factor affects the relative underweighting of investment in Quebec versus the ROC. Finally, we contrast the holdings of institutional investors located in the United Kingdom and France to bolster our conclusion that incongruent languages contribute to the underweighting of Quebec firms relative to firms in the ROC. This paper was accepted by Suraj Srinivasan, accounting.